2019
DOI: 10.1096/fj.201900462r
|View full text |Cite|
|
Sign up to set email alerts
|

In contrast to Western diet, a plant‐based, high‐fat, low‐sugar diet does not exacerbate retinal endothelial injury in streptozotocin‐induced diabetes

Abstract: Controversy remains about how diet affects the vascular endothelial dysfunction associated with disordered insulin‐glucose homeostasis. It is postulated that the type and level of certain macronutrients contribute to endothelial dysfunction in vascular diabetes complications. However, it is not well understood how specific macronutrients affect the molecular inflammatory response under conditions of hyperglycemia. Here, we examined retinal microvascular endothelial injury in streptozotocin (STZ)‐diabetic rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In agreement, our results showed that HFD-induced leukostasis after 8 weeks was positively correlated with development of acellular capillaries and decreased vascular density after 18 weeks in WT-HFD, but not in TKO mice. Interestingly, a combination of HFD and STZ for simulation of type 2 diabetes accelerated development of retinal acellular capillaries and barrier dysfunction [41,42]. Inhibition of caspase-1 or deletion of IL-1 receptor prevented IL-1β-dependent formation of acellular capillaries in retinas of type 1 diabetic mouse models [27].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, our results showed that HFD-induced leukostasis after 8 weeks was positively correlated with development of acellular capillaries and decreased vascular density after 18 weeks in WT-HFD, but not in TKO mice. Interestingly, a combination of HFD and STZ for simulation of type 2 diabetes accelerated development of retinal acellular capillaries and barrier dysfunction [41,42]. Inhibition of caspase-1 or deletion of IL-1 receptor prevented IL-1β-dependent formation of acellular capillaries in retinas of type 1 diabetic mouse models [27].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired wound healing is a major complication of diabetes mellitus (DM) and despite the associated risks, treatment strategies for diabetic-related wounds are limited. Endothelial dysfunction is an indicator of diabetes-induced macrovascular complications ( 1 , 2 ). Vascular differentiation at injury sites affects the speed of wound healing, while the homing and angiogenic differentiation of endothelial progenitor cells (EPCs) are critical for successful wound healing ( 3 ).…”
Section: Introductionmentioning
confidence: 99%